Making home visits: creativity and the embodied practices of home visiting in social work and child protection - Ferguson, Harry (SAGE Publications, 2016)
Although the home is the most common place where social work goes on, research has largely ignored the home visit. Drawing on a participant observation study of child protection work, this article reveals the complex hidden practices of social work on home visits. It is argued that home visits do not simply involve an extension of the social work organisation, policies and procedures into the domestic domain but the home constitutes a distinct sphere of practice and experience in its own right. Home visiting is shown to be a deeply embodied practice in which all the senses and emotions come into play and movement is central. Through the use of creativity, craft and improvisation practitioners ‘make’ home visits by skilfully enacting a series of transitions from the office to the doorstep, and into the house, where complex interactions with service users and their domestic space and other objects occur. Looking around houses and working with children alone in their bedrooms were common. Drawing upon sensory and mobile methods and a material culture studies approach, the article shows how effective practice was sometimes blocked and also how the home was skilfully nego¬tiated, moved around and creatively used by social workers to ensure parents were engaged with and children seen, held and kept safe.